SP5.2.7 Direct line: Implementation of a novel clinician triage service to safely prevent unnecessary surgical admissions. (9th August 2022) - Shahid, Mishal; Gurowich, Louise; Dru, Rebecca; Barton, Jessica; Lock, Kate; Hollyman, Marianne
Abstract: Introduction: With the NHS under increasing pressure, the number of patients being referred to secondary care is increasing. Ambulatory clinics are being set up to reduce admission in some patient groups. In our unit, GP referrals to General Surgery were previously being accepted to the admissions ward, without triage. A new system which allowed referrers to contact senior on-call team members was trialled to identify whether patients could be safely diverted to an ambulatory clinic, avoiding inpatient admission. Methods: A cascade triage system of referrals was trialled between September 2021 and January 2022, over a total of 30 days. Data were collected on who triaged the call, outcome of the call, and admission rate of patients. Results: Some 195 calls were analysed. Consultants were able to divert 62%(66/106) of patients to an ambulatory clinic compared to 30%(14/46) for junior doctors and 35%(15/43) for specialist nurses(p<0.001). The overall admission rate was 50%, with half of patients being successfully managed ambulatorily. Improvement was shown over time in triage by junior doctors, with 1/10 in first 10 patients versus 4/10 in the final 10 patients triaged to the ambulatory clinic. Average weekday admissions to the ward dropped from 12.1, to 7.5 on trial days. Conclusion: The trial has demonstrated senior decision makers are the most effective at directing patients to an ambulatory pathway, while junior doctors have scope to improve their skills with experience. Clinician triage is successful at reducing the number of surgical admissions when there is access to an ambulatory clinic.